IMPACT OF SELECTED PESTICIDES ON THE INCIDENCE OF YELLOW STEM BORER OF PADDY CULTIVER SWARNA MASHURI (MTU 7029) AT UTTAR DINAPUR, INDIA - CHAKRABORTY, KAUSHIK; GHOSAL, T.K.; GHOSH, JAYDEB (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
Extent of suppression of paddy yellow stem borer population by seven selected pesticides were carried out in the field of paddy cultivar Swarna mashuri (MTU 7029) during three consecutive kharif crop seasons of 2007 to 2009 at Raiganj, Uttar Dinajpur, West Bengal, India. Experiment was laid out in randomized block design and had three replications for each of the experiment years. All the treatments were found effective significantly in checking stem borer infestation leading to decrease in both dead heart (DH%) and white head (WH%) number. Numerically least damage was noted for fipronil 0.3G (5.11%DH and 4.26%WH). This was followed by Imidacloprid 17.8 SL (5.80% DH and 5.27% WH), carbofuran 3G (6, 17% DH and 5.99% WH). monocrotophos 36 WSC (8.17% DH and 7.45% WH), propenphos 50 EC (8.05% DH and 7.16% WH) cloropyriphos 20EC (8, 17% DH and 7.45% WH) and bifenthin 10 EC (9.24% DH and 8, 18% WH) in ascending order. The control plot has registered 11.07% DH and 10.80% WH respectively. In consideration of yield increase over control, maximum efficacy was registered for fipronil 0.3G (64.90%) respectively followed by (60.82%), imidacloprid 17.8 SL (60.82%), carbofuran 3G (56.07%), monocrotophos 36 WSC (53.7%) propenphos 50 EC (52.92%), chloropyriphos 20 EC(48.99%) and bifenthrin 10 EC (38.82%) in descending order.